A new CysLT1 and CysLT2 receptors-mediated anaphylaxis guinea pig model. (April 2017) - Sekioka, Tomohiko; Kadode, Michiaki; Osakada, Noriko; Fujita, Manabu; Matsumura, Naoya; Yamaura, Yoshiyuki; Nakade, Shinji; Nabe, Takeshi; Kawabata, Kazuhito
Abstract: Although the effectiveness of CysLT1 receptor antagonists on asthma has been clinically established, the effects of CysLT2 receptor antagonists are still unclear. The purpose of this study was to develop a new CysLT1 and CysLT2 receptors-mediated anaphylaxis guinea pig model using S-hexyl GSH, a γ-glutamyl transpeptidase (GTP) inhibitor, to suppress conversion of LTC4 to LTD4 . Actively sensitized guinea pigs were challenged with OVA in the absence or presence of S-hexyl GSH, and survival rate following anaphylactic response was monitored. OVA-induced fatal anaphylaxis in the absence of S-hexyl GSH was almost completely inhibited by montelukast, a CysLT1 receptor antagonist, but not by the CysLT2 receptor antagonist BayCysLT2 RA. However, under treatment with S-hexyl-GSH, the inhibitory effect of motelukast was dramatically diminished, whereas that of BayCysLT2 RA was markedly increased. The dual CysLT1/2 receptor antagonist ONO-6950 effectively inhibited anaphylactic response in both S-hexyl GSH-treated and non-treated animals. LC/MS/MS analysis revealed that S-hexyl GSH treatment actually inhibited LTC4 metabolism in the blood and lung tissues. Using S-hexyl GSH, we developed a novel CysLT1 and CysLT2 receptors-mediated anaphylaxis guinea pig model that can be useful for not only screening both CysLT2 and CysLT1/2 receptors antagonists, but also for functional analysis of CysLT2 receptors. Highlights: Anaphylaxis model mediated via both CysLT1 and CysLT2 receptors was developed. Dual CysLT1/2 receptor antagonist ONO-6950 inhibited the anaphylactic response. This model is useful for analyzing functional roles of CysLT2 receptors in asthma.